Acute kidney injury in the pediatric ICU of a tertiary care hospital: Cross sectional observational study - Suprita Kalra; Punam Bajracharya; Sandeep Dhingra; Amit Sood (Wolters Kluwer Medknow Publications, 2018)
Objective: Acute kidney injury shown to be commonest complication in critically ill children admitted to the PICU. KDIGO classification and definition now used universally. We undertook prospective observational study to study the etiology and maximum stage of AKI as defined by KDIGO, its complications and outcomes. Materials and Methods: All children admitted to the PICU were included in the study. The diagnosis of sepsis and MODS was made according to the standard International guidelines. The patients were followed up till discharge/death. All children were screened for AKI at admission and subsequently using serum creatinine measured by modified Jaffe's method and urine output measurement. Results: 197 children were admitted to PICU. 38 (19.28%) developed AKI and 6 (15.78%) developed stage III AKI. Malignancies, serious neurological and renal disorders and post complex surgeries accounted for most of the cases with AKI. Six were admitted with primary renal condition. Sepsis with or without MODS was seen in 12 patients with AKI and in 8 without AKI.21 children with AKI and 3 children were exposed to nephrotoxic drugs. 23 Children with AKI required inotropic support. Children with AKI had ALOS in PICU of 9.86 days while ALOS in children without AKI was 6.23 days.18 children with AKI died (47.36%) while 36 (21.38%) with no AKI expired. Conclusions: AKI in children in the PICUs of referral hospitals in the armed forces have varied etiologies and presentations. These children require early identification and management with close monitoring to prevent long term renal morbidity and mortality.